24) \( 16^{2 p-3} \cdot 4^{-2 p}=2^{4} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
Let's first rewrite all terms in the equation using base 2. We know that \( 16 = 2^4 \) and \( 4 = 2^2 \). So, we rewrite the equation: \[ 16^{2p-3} \cdot 4^{-2p} = (2^4)^{2p-3} \cdot (2^2)^{-2p} \] This simplifies to: \[ 2^{4(2p-3)} \cdot 2^{-4p} = 2^{4p - 12} \cdot 2^{-4p} \] Now, combine the exponents: \[ 2^{4p - 12 - 4p} = 2^{-12} \] Thus, we have: \[ 2^{-12} = 2^4 \] Since the bases are the same, we can set the exponents equal to each other: \[ -12 = 4 \] But this is clearly not true, so we must have made a mistake or more likely, there are no values of \( p \) that will satisfy this equation. It leads to a contradiction. In summary, this equation has no solution since the exponents cannot equal each other.